Development of Current Stick Teaching Aids to Improve Students' Generic Science Skills - Nur Khoiri; Choirul Huda; Joko Saefan; Wawan Kurniawan (STKIP Singkawang, 2021)
The study aimed to develop the Current Stick teaching aids and determine its effectiveness to improve students’ generic skills. The type of research is development research which involved 180 students of class X SMAN in Blora were chosen through cluster random sampling. The instrument used to collect the data was a validated question sheet from the assessment of students’ practicum report in using Current Stick teaching aids and the observation sheet. The instruments were addressed to students from the control class and experimental class. The obtained data were tabulated and analyzed by using t-test. The result shows that the experimental class achieved an average percentage of generic science skills of 77.2%, while the control class reached 66.4%. It reveals that the difference in the percentage of generic science skills is the result of using Current Stick teaching aids. Based on the results and discussion, it was found that the development of Current Stick teaching aid is effective to improve students' Generic Science skills.